Political Leader Survival: Does Competence Matter? - Shu Yu; Richard Jong-A-Pin (Center for Economic Studies and ifo Institute (CESifo), 2013)
We examine whether economic and military competence of political leaders affect their duration in office. We introduce leader heterogeneity in the selectorate theory of Bueno de Mesquita et al. (2003) and derive the hypothesis that in the presence of a revolutionary threat, economic competence is negatively related to political survival, but that the effect is moderated by the size of the winning coalition. As military and economic competence are negatively correlated, the opposite holds for military competence. We present empirical estimates using proxies for military and economic competence in a parametric Weibull duration model that support our theoretical predictions.
Keywords: D02; D72; D74; O12; 330; political leader; survival analysis; leader competence; selectorate theory